2002
DOI: 10.1038/sj.cgt.7700510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of safety, delivery, and efficacy of two oncolytic herpes viruses (G207 and NV1020) for peritoneal cancer

Abstract: G207 and NV1020 are two replication -competent, multimutant oncolytic herpes simplex viruses evaluated in the current studies for their anticancer effects in the treatment of gastric cancer. Deletion of both 1 34.5 genes and inactivation of ICP6 ( ribonucleotide reductase ) allows G207 to selectively replicate within tumor cells. NV1020 is another attenuated recombinant herpes virus with deletions of the HSV joint region, with deletion of only one copy of the 1 34.5 gene, and with the ICP6 gene intact. In vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…A growing body of preclinical and clinical data suggests that oncolytic viral therapy could be an effective therapeutic modality in the treatment of advanced cancer. [5][6][7][8][9][10][11] Various strains of viruses, such as adenovirus, 12 herpes simplex virus, 13 Newcastle disease virus, measles virus, vesicular stomatitis virus and vaccinia virus 14 are being analyzed for their oncolytic capacity; some of these viruses have progressed to the clinical trial phase. Herpes simplex virus type 1 (HSV 1) is an ideal candidate for oncolytic viral therapy because of the following reasons: (a) it infects a broad range of hosts; (b) it causes lyses of the host cell at the end of viral replication; (c) it has a very large genome and therefore harbors many non-essential genes, mostly related to neuroinvasiveness that are expendable and can be replaced during the recombinant engineering process; (d) it can be controlled by antiviral drugs in the event of uncontrolled replication; and (e) its genome remains as an episome and does not incorporate in to the host genome, avoiding the risk of introducing mutations.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of preclinical and clinical data suggests that oncolytic viral therapy could be an effective therapeutic modality in the treatment of advanced cancer. [5][6][7][8][9][10][11] Various strains of viruses, such as adenovirus, 12 herpes simplex virus, 13 Newcastle disease virus, measles virus, vesicular stomatitis virus and vaccinia virus 14 are being analyzed for their oncolytic capacity; some of these viruses have progressed to the clinical trial phase. Herpes simplex virus type 1 (HSV 1) is an ideal candidate for oncolytic viral therapy because of the following reasons: (a) it infects a broad range of hosts; (b) it causes lyses of the host cell at the end of viral replication; (c) it has a very large genome and therefore harbors many non-essential genes, mostly related to neuroinvasiveness that are expendable and can be replaced during the recombinant engineering process; (d) it can be controlled by antiviral drugs in the event of uncontrolled replication; and (e) its genome remains as an episome and does not incorporate in to the host genome, avoiding the risk of introducing mutations.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison with panel (b), fractionated dosing of UVinactivated virus on day 0 was also administered to tumors of similar size (c, UV-NV1066); for panel b vs. c, P ¼ .003. tion is thus difference in virus potency, since others have found G207 to be less potent than NV1020. 50 Importantly, Cinatl et al also demonstrated an antitumor effect following intravenous administration of virus that was potentiated by the addition of vincristine. Others have found a synergy between G207 and irradiation, at least in part due to the radiation-induced upregulation of cellular ribonucleotide reductase.…”
Section: Discussionmentioning
confidence: 99%
“…Both rHSV 1716 and G207 were effective in animal models of malignant peritoneal disease induced by injection of human ovarian cancer cells (14,16). Intraperitoneal administration of G207 was also reported to have therapeutic potential against peritoneal tumors (17). rHSV R3616, an ICP34.5 deficient, replication-restricted HSV-1 was equally effective against chemotherapy-sensitive and -resistant ovarian cancer cells in vitro and in vivo (16).…”
Section: Discussionmentioning
confidence: 99%